The Effect of Employee Retention and Work Environment on Employee Performance in Jekan Raya District, Palangka Raya - Dimer Merpati Umbing Umbing (Jurnal Manajemen Sains dan Organisasi, 2022)
Objective - This study aims to analyze the effect of organizational culture and workethics on employee performance.Design/Methodology/Approach - The analysis was carried out at DIY PalangkaRaya Mall, which is a one-stop shop and is crowded with visitors. This research wasconducted quantitatively and questionnaires were distributed to 35 respondents whowere DIY employees.Research findings – The results of the statistical analysis using SPSS 22.0 statedthat 73% had a very important role in organizational culture and work ethics inimproving performance. the implications of the results can apply an organizationalculture system according to DIY Palangka Raya Mall and apply work ethicsproperly and correctly. Future research can adopt this research to improveemployee performance.